Братство спецназа: повесть / Сергей Самаров - Самаров Сергей Васильевич (Спецназ ГРУ, 2003)
Экземпляры: Ф. 12 (20210508) / Инвентарный номер: 38649 / Цена: 25.00 / Сис.шифр: 84(2Рос=Рус)6 / Авт.знак: С 17 / ГРНТИ: 17.82 / ББК: 84(2Рос=Рус)6